Simultaneous Mid-Infrared Gas Sensing and Upconversion Based on Third Harmonic Generation in Cascaded Waveguides - Jianxing Pan; Zhenxing Chen; Tianye Huang; Shuwen Zeng; Zhuo Cheng; Pan Huang; Xiang Zhao; Perry Ping Shum; Gilberto Brambilla (IEEE Photonics Journal)
The performance of conventional gas sensors based on light absorption in the mid-infrared are limited by the high-cost and low efficiency of photon detection at these wavelengths. In this paper, cascaded suspended waveguides are proposed and analyzed for mid-infrared gas sensing with enhanced detection limit. The cascaded structure contains two sections in which the first part is optimized for light absorption and the other one is tailored to satisfy the phase matching condition for third harmonic generation toward near-infrared wavelengths. In this configuration, the input mid-infrared light firstly experiences “fingerprint” frequency absorption in the on-chip gas chamber. Consequently, the residuary light produces third harmonic radiation in the second section. Benefiting from the nonlinear relation between pump and harmonic power, the sensitivity of the sensor is significantly improved. Moreover, the signal is up converted from mid-infrared to near-infrared and thus it can be easily detected by efficient near-infrared detectors. The results show that the detection limit can reach the order of nmol/L and the absorption lengths can be reduced to three times shorter comparing to direct mid-infrared detection. The proposed configuration has great potential for high performance on-chip gas sensing.